Pottery Making and Communities During the 5th Millennium BCE in Fars Province, Southwestern Iran - Miki, Takehiro (Archaeopress Publishing, 2022)
This book explores pottery making and communities during the Bakun period (c. 5000 - 4000 BCE) in the Kur River Basin, Fars province, southwestern Iran, through the analysis of ceramic materials collected at Tall-e Jari A, Tall-e Gap, and Tall-e Bakun A & B. Firstly, it reconsiders the stratigraphy and radiocarbon dates of the four sites by reviewing the descriptions of excavation trenches, then presents a new chronological relationship between the sites. The book sets out diachronic changes in the the Bakun pottery quantitatively, namely the increase of black-on-buff ware and the gradual shift of vessel forms. It also presents analyses of pottery-making techniques, painting skills, petrography, and geochemistry and clarifies minor changes in the chaînes opératoires and major changes in painting skill. Finally, the book discusses the organisation of pottery production from a relational perspective. It concludes that the more fixed community of pottery making imposed longer apprenticeship periods and that social inequality also increased.